Repurposing Kir6/SUR2 Channel Activator Minoxidil to Arrests Growth of Gynecologic Cancers - Fukushiro-Lopes, Daniela; Hegel, Alexandra D.; Russo, Angela; Senyuk, Vitalyi; Liotta, Margaret; Beeson, Gyda C.; Beeson, Craig C.; Burdette, Joanna; Potkul, Ronald K.; Gentile, Saverio (Frontiers in Pharmacology, 2020)
Gynecologic cancers, are among the most lethal cancers found in women and, advanced stage cancers are still a treatment challenge. Ion channels are known to contribute to cellular homeostasis in all cells and mounting evidence indicates that ion channels could be considered potential therapeutic targets against cancer. Nevertheless, the pharmacologic effect of targeting ion channels in cancer is still understudied. We found that the expression of Kir6.2/SUR2 potassium channel is a potential favorable prognostic factor in gynecologic cancers. Also, pharmacological stimulation of the Kir6.2/SUR2 channel activity with the selective activator molecule minoxidil arrests tumor growth in a xenograft model of ovarian cancer. Investigation on the mechanism linking the Kir6.2/SUR2 to tumor growth revealed that minoxidil alters the metabolic and oxidative state of cancer cells by producing mitochondrial disruption and extensive DNA damage. Consequently, application of minoxidil results in activation of a caspase-3 independent cell death pathway. Our data show that repurposing of FDA approved K+ channel activators may represent a novel, safe adjuvant therapeutic approach to traditional chemotherapy for the treatment of gynecologic cancers.